Aplicación de una auditoría de gestión administrativa a la cooperativa de ahorro y crédito cámara de comercio de Latacunga, ubicada en la parroquia la matriz, del cantón Latacunga, provincia de Cotopaxi, al período del 01 de enero al 31 de diciembre de 2012 - Herrera Quintana, María Cristina (2014)
The Management Audit is the objective and systematic checkup of evidence made to an enterprise, in order to provide an independent assessment of the performance of an activity that aims to improve accountability to the user and to simplify the process of decision making by the responsible for administering or arranging corrective tasks. Due to its characteristics, the Management Audit is a key driver of development tool organizations which involves three basic features: achieving goals, the process to accomplish them, the resources used. Performing Administrative Management Audit will significantlysupport the Cooperative since through it may improve the work done by the employees to have a clear view of the institutional objectives , as well as improve control of activities chaired by the Directors, will optimize better the resources of the Cooperative considering policies under the same ones.